Morphological and molecular characterization of Udonella brasiliensis n. sp. (Monogenoidea), an epibiont on Caligus sp. parasite of Ariidae from the southeastern coast of Brazil. (August 2021) - Soares, Geusivam B.; Domingues, Marcus V.; Adriano, Edson A.
Abstract: The present study describes Udonella brasiliensis n. sp., an epibiont found on Caligus sp., a parasite the ariids Genidens barbus (Lacepède) and Aspistor luniscutis (Valenciennes), caught on the coast of the state of São Paulo, Brazil. Morphological and molecular analyses (partial 18S rDNA) were carried out. The morphological data showed that U. brasiliensis n. sp. can be distinguished from current valid species by its morphometric attributes ( e.g., body, pharynx, ovary and testis), while the molecular information supports the proposal of a new species. The 18S rDNA phylogenetic analysis shows a close relationship between the new species and Udonella australis Carvajal & Sepulveda, in a subclade formed of species that parasitize South American fish. Finally, this study also discusses a scenario of initial irradiation for udonellids. Graphical abstract: Unlabelled Image Highlights: Udonella brasiliensis n. sp. is described by using an integrative taxonomic approach. The new species differs from other Udonella spp. based on morphological and molecular data. The new species is closely related to udonellid that parasitize South American fish. The study also discusses a scenario of initial irradiation for udonellids.